2021
DOI: 10.1039/d1ra05369h
|View full text |Cite
|
Sign up to set email alerts
|

Stable cycling of Prussian blue/Zn battery in a nonflammable aqueous/organic hybrid electrolyte

Abstract: Aqueous FeHCF/Zn battery with a hybrid electrolyte exhibits ultralong cycle life with 51.4% capacity retention after 19 000 cycles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
(40 reference statements)
0
5
0
Order By: Relevance
“…[48,72,73] On the basis of maintaining the original advantages of individual components and relativity high ionic conductivity, this strategy has the possibility of improving the interface contact between electrodes and electrolytes. [74][75][76][77] In addition, the selection scope of solvents can be significantly broadened and the obviously expanded ESW can meet the requirements of more electrode materials. Unlike the low-temperature organic electrolytes using a small amount and efficient additive, hybrid electrolytes generally employ a certain amount of organic cosolvents to present an obvious effect.…”
Section: Solvent Optimizationmentioning
confidence: 99%
“…[48,72,73] On the basis of maintaining the original advantages of individual components and relativity high ionic conductivity, this strategy has the possibility of improving the interface contact between electrodes and electrolytes. [74][75][76][77] In addition, the selection scope of solvents can be significantly broadened and the obviously expanded ESW can meet the requirements of more electrode materials. Unlike the low-temperature organic electrolytes using a small amount and efficient additive, hybrid electrolytes generally employ a certain amount of organic cosolvents to present an obvious effect.…”
Section: Solvent Optimizationmentioning
confidence: 99%
“…Although rechargeable aqueous batteries are attracting increasing attentions due to their low cost, high safety, environmentally friendly nature, and improved rate performance, the "free water" (the term "free water" indicates water molecules interacting solely with other water molecules) [139] molecules in aqueous electrolytes strongly limit the electrochemical stability window of the electrolyte and trigger multiple side reactions, thus affecting cell performance upon cycling. In order to suppress the activity of "free water" molecules and expand the electrochemical stability window, novel electrolytes and components have been proposed, including high concentrated electrolytes or "water-in-salt/gel" electrolytes, [78,82,87,95,97,105,107,140] hybrid electrolytes, [65,66,74,75,77,78,[81][82][83]85,87,95,107,141,142] solid polymer electrolyte, [103] and additives, [84,86,88,89] to improve the electrochemical performances of AZIBs. D. Kim et al [140] reported that the cycling performance of ZnHCF in concentrated electrolyte (3 M Zn(NO 3 ) 2 ) was superior to that observed in the diluted system (1 M Zn(NO 3 ) 2 ), as a consequence of the decrease in the hydration number and radius of the zinc ions in the concentrated electrolyte.…”
Section: Electrolyte Optimizationmentioning
confidence: 99%
“…It was observed that VC not only plays an important role in extending the electrochemical stability window, but also prevents the dissolution of the cathode material. Indeed, the aqueous FeHCF/Zn cell exhibited a good cycling stability with 60 % capacity retention after 4000 cycles when cycled at 10 C. Xu et al [86] proposed a hybrid aqueous electrolyte with mixed solvent of water and acetonitrile (ACN). Since ACN can form strong hydrogen-bonding interaction with water, an extension of the electrochemical windows was observed, as well as a decrease in side-reactions of the aqueous electrolyte.…”
Section: Electrolyte Optimizationmentioning
confidence: 99%
“…The schematics within the figure are reprinted with permission from refs. [10,12–16] Copyright 2020, Royal Society of Chemistry, Copyright 2022, Elsevier, Copyright 2015, American Association for the Advancement of Science, Copyright 2020, Shanghai Jiao Tong Univ Press, Copyright 2021, Royal Society of Chemistry.…”
Section: Introductionmentioning
confidence: 99%